PHYTOCHEMICAL AND PHARMACOLOGICAL STUDY ON SELECTED INDONESIAN WEEDS EXTRACTS: A NOVEL INSIGHT TO ANTI-SHIGELLOSIS - KUSUMA, SRI AGUNG FITRI; ZUHROTUN, ADE; NOARI, DWI RAHMAT (International Journal of Applied Pharmaceutics, 2022)
Objective: Elephant grass (Pennisetum purpureum S.), weed grass (Imperata cylindrica L.), pearl grass (Hedyotis corymbosa L.) and nut grass (Cyperus rotundus L.) are selected weeds found in Indonesia which have been used as ruminants feeding with a complete diet component and evidently reported that bioactive contents of weeds provide more protection to microbial attack than that of crops. This has led to an increase interest in the investigation of weed extracts as anti-shigellosis agents for humans and animals, but there is still no data regarding on phytochemical and pharmacological of our selected weeds as an anti-shigellosis. Therefore, the objectives of this study was to analyze phytochemical and anti-shigellosis properties of those selected weeds towards sensitive (S) and resistant S. dysentriae (R) strains of ampicillin, chloramphenicol, and cotrimoxazoles. Methods: Phytochemical screening was done using the standard method and further analyzed by thin-layer chromatography (TLC). The anti-shigellosis activity was evaluated using the agar diffusion method; meanwhile, the minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) value was determined using the microdilution method. Results: In general, weeds contain flavonoids, steroid, and quinone compounds. The resulted anti-shigellosis showed that all weed extracts produced higher inhibition to sensitive than resistant strains. The MIC-MBC values of each weed on sensitive and resistant, respectively, were as follow: P. purpureum S (S=≥1.25%; R=≥2.5% w/v); I. cylindrica (S=≥5.0%; R=≥ 2.5-10.0%w/v); H. corymbosa (S=≥2.5%; R=≥2.5-10%w/v); and C. rotundus (S=≥2.5-5.0%; R=≥5.0-10%w/v). From these data, all of these weeds have the potential to complement antibiotics that are no longer effective in the treatment of shigella infections. Conclusion: In summary, P. purpureum extract could be promoted as a novel supplement phytopharmaceutical for the treatment of bacillary dysentery.